"The role of accounting and administrative control in reducing loan default in public Syrian banks" A field study in public banks in the Syrian Arab Republic (Damascus University Journal for the economic and Political sciences, 2021)
The research aims to know the role of accounting and administrative control (the role of governance mechanisms) in reducing loan default in public banks in the Syrian Arab Republic. To achieve this goal, the researcher has tried (1) to know the most important causes of loans in public banks faltering during the previous stage, (2) to know whether governance mechanisms are performing their functions in public banks at the present time efficiently and effectively, (3) knowing the extent of the contribution of efficient and effective application of mechanisms Governance is to reduce the failure of loans in public banks, (4) and know which mechanisms of governance can be more effective in reducing the failure of loans in public banks.To achieve the goals of the research and test its hypotheses, data was collected through a survey study using the questionnaire as a tool to collect data on a sample of employees in banking risk directorates, internal control directorates, internal audit directorates, and credit and lending directorates in the departments of public banks in Damascus Governorate, so that the final sample size reached (100) employees of the specialists, then the questionnaires were analyzed and hypotheses tested using a set of appropriate statistical methods using the SPSS program.The research reached a set of results, the most important of which were:The causes of non-performing loans in public banks during the previous stage cannot be limited to one party.• The most important reasons for the failure of loans in public banks during the previous stage related to the bank granting the credit were (1) lack of accurate, clear, periodic and renewed customer inquiries, (2) lack of diversification in the loan portfolio and the allocation of a large proportion of loans and credit facilities to one borrower, ( 3) Failure to monitor the use of loans granted to clients, and to use them for purposes not granted for him, (4) the lack of integrity of those responsible for granting credit facilities.• Governance mechanisms in public banks do not currently function efficiently and effectively.• The efficient and effective application of governance mechanisms contributes to reducing loan default in public banks.• The degree of efficiency and effectiveness of governance mechanisms varies in reducing loan default in public banks.• "Legislation and laws" occupies the first place in importance from the point of view of the study sample, which is one of the external governance mechanisms.• The "Board of Directors" is ranked second in importance from the point of view of the study sample, and it is one of the internal governance mechanisms.
Keywords: accounting and management control; governance; governance mechanisms; non-performing loans; public banks